Expression and Characteristics of Two Glucose-Tolerant GH1 β-glucosidases From Actinomadura amylolytica YIM 77502T for Promoting Cellulose Degradation - Yin, Yi-Rui; Sang, Peng; Xian, Wen-Dong; Li, Xin; Jiao, Jian-Yu; Liu, Lan; Hozzein, Wael N.; Xiao, Min; Li, Wen-Jun (Frontiers in Microbiology, 2018)
The bioconversion of lignocellulose in various industrial processes, such as biofuel production, requires the degradation of cellulose. Actinomadura amylolytica YIM 77502T is an aerobic, gram-positive actinomycete that can efficiently degrade crystalline cellulose by extracellular cellulases. Genomic analysis of A. amylolytica identified 9 cellulase and 11 β-glucosidase genes that could potentially encode proteins that digest cellulose. Extracellular proteome characterization of A. amylolytica cell-free culture supernatant by liquid chromatography tandem mass spectrometry analysis revealed that 4 of these cellulases and 2 of these β-glucosidases functioned during cellulose hydrolysis. Thin-layer chromatography analysis revealed extracellular β-glucosidases play a major role in CMC degradation of products in culture supernatants. In this study, 2 of the identified secreted β-glucosidases, AaBGL1 and AaBGL2, were functionally expressed in Escherichia coli and found to have β-glucosidase activity with wide substrate specificities, including for pNPG, pNPC, and cellobiose. Moreover, AaBGL1 and AaBGL2 had high tolerances for glucose. After adding these β-glucosidases to commercial cellulases, the degradation rates of CMC, Avicel, birch sawdust, and corncob powder increased by 37, 42, 33, and 9%, respectively. Overall, this work identifies an alternative potential source of β-glucosidases with potential applications in commercial cellulose utilization and the bioenergy industry.